New sivaladapid primate from Lower Siwalik deposits surrounding Ramnagar (Jammu and Kashmir State), India. Issue 102 (January 2017) - Gilbert, Christopher C.; Patel, Biren A.; Singh, N. Premjit; Campisano, Christopher J.; Fleagle, John G.; Rust, Kathleen L.; Patnaik, Rajeev
Abstract: Over the past century, numerous vertebrate fossils collected near the town of Ramnagar, India, have proven to be important for understanding the evolution and biogeography of many mammalian groups. Primates from Ramnagar, though rare, include a number of hominoid specimens attributable to Sivapithecus, as well as a single published mandibular fragment preserving the P4 -M1 of the Miocene adapoid Sivaladapis palaeindicus . Since 2010, we have renewed fossil prospecting in the Lower Siwalik deposits near Ramnagar in an attempt to better understand the evolution, biogeographic timing, and paleoclimatic context of mammalian radiations in Asia, with a particular focus on primates. Our explorations have resulted in the identification of new fossil localities, including the site of Sunetar. The age of Sunetar and the Ramnagar region, in general, is tentatively dated between 14 and 11 Ma. In 2014, a partial right mandible of a sivaladapid primate was recovered at Sunetar, preserving the corpus with P4 roots and worn M1 -M3 dentition. Although sivaladapids are known by numerous specimens of two genera ( Sivaladapis and Indraloris ) at Lower Siwalik sites on the Potwar Plateau (Pakistan) and at the Middle Siwalik locality of Haritalyangar (India), this new specimen is just the second sivaladapid recovered from the Ramnagar region. Our analyses suggest that the new specimen is distinct from all other sivaladapids, and we therefore describe it as a new genus and species close to the base of the Sivaladapinae.